2018
DOI: 10.1252/jcej.17we235
|View full text |Cite
|
Sign up to set email alerts
|

Silica-Based Membranes with Molecular-Net-Sieving Properties: Development and Applications

Abstract: Over the past several decades, inorganic membranes composed of zeolite, silica, carbon, and metal/organic frameworks (MOF) have improved dramatically in terms of fabrication and application. Pure silica (SiO 2 ) and organosilica membranes for use in molecular separation are the focus of this review. First, the fabrication of these silica-based membranes is outlined to highlight the great progress achieved in sol-gel and CVD processing. Then, applications in gas-and liquid-phase separations and an evaluation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 61 publications
(36 citation statements)
references
References 69 publications
(94 reference statements)
0
36
0
Order By: Relevance
“…Organosilica bis(triethoxysilyl)ethane (BTESE)-derived membranes with -CH 2 CH 2 -linking units between two Si atoms (Spacer technique) were applied to gas separation 14 and showed higher gas permeance than silica membranes prepared from tetraethoxysilane (TEOS) consisting of one Si atom. 15,16 BTESE-derived membranes with layered structures consisting of BTESE/SiO 2 -ZrO 2 /α-Al 2 O 3 layers are generally prepared by coating BTESE-derived sol as a top layer onto a SiO 2 -ZrO 2 intermediate layer, 17 which is also formed on a porous α-Al 2 O 3 support. These membranes have demonstrated high permeance ratios for H 2 /C 3 H 8 (>10 3 ) and N 2 /CF 4 (>60) due to the uniform pore sizes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Organosilica bis(triethoxysilyl)ethane (BTESE)-derived membranes with -CH 2 CH 2 -linking units between two Si atoms (Spacer technique) were applied to gas separation 14 and showed higher gas permeance than silica membranes prepared from tetraethoxysilane (TEOS) consisting of one Si atom. 15,16 BTESE-derived membranes with layered structures consisting of BTESE/SiO 2 -ZrO 2 /α-Al 2 O 3 layers are generally prepared by coating BTESE-derived sol as a top layer onto a SiO 2 -ZrO 2 intermediate layer, 17 which is also formed on a porous α-Al 2 O 3 support. These membranes have demonstrated high permeance ratios for H 2 /C 3 H 8 (>10 3 ) and N 2 /CF 4 (>60) due to the uniform pore sizes.…”
mentioning
confidence: 99%
“…Regarding the intermediate layers, microporous SiO 2 -ZrO 2 membranes were prepared via the sol-gel method. [13][14][15][16][17][18][19][20][21] SiO 2 -ZrO 2 membranes have a great advantage in pore size control within a wide range from subnanometer to several nanometers with different Si/Zr ratios. 17,20 It has been reported that SiO 2 -ZrO 2 membranes with excellent selectivity and stability have been applied to various separation processes such as nanofiltration, 17 pervaporation, 21 and gas separation.…”
mentioning
confidence: 99%
“…To avoid difficulty and complexity, an excess amount of feed, which often reaches 100‐fold that of the permeated gas, is generally fed to a membrane module in the quest for a negligible change in the upstream flow rate and concentration along the membrane, 11,18 while single‐gas permeance can be obtained without the use of a significant amount of feed due to the lack of a change in the upstream partial pressure. Due to active research in recent years, membrane permeance has improved significantly to reach values larger than 10 −6 mol/(m 2 s Pa) 19‐21 . Recently, we also reported water vapor permeance of 5.5 × 10 −6 mol/(m 2 s Pa) and water flux of 37 kg/(m 2 h) during water/nitrogen separation at 150°C using a 1,2‐bis(triethoxysilyl) ethane‐derived silica membrane, which corresponds to permeated water flow rate of 2.4 L/min (standard temperature and pressure), even though the experiment was performed with a moderate partial pressure difference across the membrane of 107 kPa and a small membrane area of 0.00314 m 2 10 .…”
Section: Introductionmentioning
confidence: 92%
“…13 Membrane processes also provide a signicant, convenient, and sustainable solution for H 2 and O 2 separation. [14][15][16][17][18] In recent years, several types of membranes have been developed for the iodine-sulfur cycle. 4,[19][20][21][22][23][24][25][26][27][28] Myagmarjav et al reported that a hexyltrimethoxysilane (HTMOS) derived silica membrane achieved H 2 permeance on the order of 10 À7 mol m À2 s À1 Pa À1 with H 2 /HI selectivity of more than 175.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, we reported several classes of inorganic membrane materials/metal oxides employed in membrane reactors for O 2 /SO 3 separation. 3,5 SiO 2 membranes, due to their excellent thermal stability and high gas selectivity, 17,32 were rst used by our team for O 2 /SO 2 separation in 2015. 3 Bis(triethoxysilyl)ethane (BTESE)-derived membranes, particularly those fabricated under high temperatures, have demonstrated high oxidation resistance and exhibited an O 2 / SO 3 selectivity of 10 with an O 2 permeance of 2.5 Â 10 À8 mol m À2 s À1 Pa À1 .…”
Section: Introductionmentioning
confidence: 99%